Atypical central retinal artery occlusion: an uncommon cause of retinopathy and visual loss in dermatomyositis. (25th September 2015) - Sharma, Mukta; Prashar, Aditi; Tuli, Rajiv; Sharma, Rattan K.; Mahajan, Vikram K.
Abstract: Several ophthalmic manifestations in patients with dermatomyositis have been described but involvement of the retina is rare. A 39‐year‐old man diagnosed with dermatomysitis had developed sudden painless visual loss in the left eye. He was non‐diabetic and non‐hypertensive. He was on treatment with systemic prednisolone (50 mg/day) and methotrexate (7.5 mg/day) for dermatomyositis. His visual acuity was finger counting at 2 feet in the left eye and 6/6 in the right eye. Left fundus showed slight blurring of the optic disc margins, large peripapillary flame‐shaped haemorrhages and extensive area of opacification suggestive of central retinal artery occlusion (CRAO) with sparing of the area supplied by the cilioretinal artery. The exact pathomechanism of CRAO in dermatomyositis remains poorly elucidated. The infarctive events following endothelial damage and platelet thrombi occurring in arterioles and capillaries of retina, optic disc and choriocapillaries causing ischemia/infarction have been suggested as possible reasons. However, central artery occlusion from high intraocular pressure from marked (heliotrope) orbital edema appears more plausible in our case. The degree of retinal damage is variable when CRAO lasts between 105 and 240 min and irreversible profound visual loss may occur from its occlusion lasting for more than 240 min. A prompt ophthalmological opinion/management is recommended to limit its progression.